Tantangan Implementasi HAM Di Papua Sebagai Negara Yang Demokratis - Ali Syarif, Kurnia (EDUSOS: Jurnal Edukasi dan Ilmu Sosial, 2024)
The implementation of human rights in Papua presents a major challenge for the Indonesian government. This challenge is further complicated by Indonesia's position as a democratic country where freedom of speech must be given to the community. This study uses a normative legal research methodology to explore the challenges and potential solutions to human rights implementation in Papua. It focuses on the legal framework, institutional mechanisms, and practical strategies for implementing human rights in Papua. The findings of this study highlight the need for a comprehensive approach that addresses the root causes of the challenges faced in implementing human rights in Papua. The study recommends the establishment of a special human rights implementation unit, strengthening institutional mechanisms, and increasing community participation in the implementation process. Overall, this study contributes to the ongoing discourse on human rights implementation in Papua and provides valuable insights for policymakers, practitioners, and researchers in the field of human rights.